THE MAIN CHARACTERISTICS OF PERSON’S SELF-REGULATION IN THE PROCESS OF PROVIDING THE PSYCHOLOGICAL WELLBEING DURING COVID-19 - Avanesyan, Hrant; Asriyan, Elina; Papoyan, Seda (Modern Psychology, 2022)
Article is devoted to the problem of psychological wellbeing the context of stress situation and the factors which have an impact on it. In particular, the process of self-regulation, psychological capital and their main components are theoretically analyzed. The research part consists of two independent stages. The first study aimed at revealing of correlation between self-regulation and components of psychological capital. Results show a high correlative link between them. Another study was held to find out the main attitudes towards Covid-19 as a stress factor. Results show the supportive role of self-regulative process (especially tendency to action) as the resource of psychological wellbeing protection during stress and uncertainties.